(untitled) (International journal of artificial intelligence, 2025)
This article explores the formation and development of Roman grammatical schools and their significance in modern linguistics. It examines the connections between ancient Roman grammatical traditions and Greek linguistic thought, highlighting their influence on subsequent linguistic theories. The study also compares the morphological and syntactic views of Roman grammarians with contemporary linguistic paradigms. The findings emphasize the enduring contribution of Roman linguistic heritage to the evolution of modern grammatical theory.